THE ROLE OF FINANCIAL RATIO ANALYSIS SEEN IN TERMS OF LIQUIDITY, SOLVABILITY AND PROFITABILITY IN MEETING THE STANDARDS OF FINANCIAL RATIO FOR COMPANY HEALTH(CASE STUDY AT PT. IGASAR) - Dewi Mayasari; Rini Yulia (Journal Dialectica (Journal of Accounting Research), 2026)
Research Objectives: The objective of this study is to evaluate the financial health level of PT. Igasar during the period 2014–2016 by analyzing financial ratios, specifically liquidity, solvency, and profitability ratios, and assessing whether these ratios meet the standard benchmarks of a healthy company. Design/ Methodology / Approach Research: This study employs a descriptive quantitative approach using secondary data derived from the company’s financial statements (balance sheets and income statements) for the period 2014–2016. Data collection is conducted through documentation techniques. The analysis method includes: 1. Financial ratio analysis (liquidity, solvency, and profitability ratios), 2. Comparative analysis, comparing company ratios against standard financial benchmarks. The evaluation is based on established financial ratio standards to determine the company’s health level. Research Results: The findings indicate that PT. Igasar’s financial performance during 2014–2016 is generally unhealthy, as reflected in all three ratio categories:1. Liquidity: The current ratio, quick ratio, and cash ratio consistently fall below standard benchmarks, indicating the company’s inability to meet short-term obligations effectively. 2. Solvency:The debt-to-asset ratio and debt-to-equity ratio remain high throughout the observed period, suggesting excessive reliance on debt financing and high financial risk. 3. Profitability: Profitability ratios (Net Profit Margin, Return on Assets, and Return on Equity) do not meet standard levels. Although there is a slight improvement after 2014 (from loss to profit), overall performance remains below healthy standards. ​Implications of Research Results: The results imply that PT. Igasar faces significant financial management challenges, including: Weak short-term financial stability (liquidity issues), High dependency on external financing (solvency risk), and Inefficient utilization of assets and capital in generating profits. These findings suggest the need for: Improved financial management and cost control, Better coordination across organizational divisions, and strategic efforts to enhance operational efficiency and competitiveness. Overall, financial ratio analysis proves to be an effective tool for evaluating and monitoring company health and supporting managerial decision-making.